2003
DOI: 10.1046/j.1444-2906.2003.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on resting egg formation of the tropical SS-type rotifer Brachionus rotundiformis Tschugunoff

Abstract: Tropical minute rotifer strains (SS‐type) induce mixis at 30–35°C but sexual reproduction and resting egg formation do not proceed well due to rapid environmental change. The present study examined the effect of temperature regulation on rotifer Brachionus rotundiformis (Langkawi strain, SS‐type) resting egg formation in small (500 mL in culture volume)‐ and large‐scale (500 L in culture volume) experiments. Rotifers were cultured at 30°C in 15–17 p.p.t. seawater with an initial density of 1 individual (ind.)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…We hypothesized that resting egg formation and hatching associated with seasonal changes of salinity could affect descendent sexual reproduction. In order to test this hypothesis, culture conditions (i.e., temperature and food) were adjusted to induce active sexual reproduction of B. rotundiformis according to previous studies (Assavaaree et al, 2003;Hagiwara et al, , 1995Hirayama and Rumengan, 1993). In the presence of abundant and high quality food and an optimal temperature for rotifer population growth, the rotifers in the current study showed strong population growth compared to a natural population (<0.5 ind/mL, Snell et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We hypothesized that resting egg formation and hatching associated with seasonal changes of salinity could affect descendent sexual reproduction. In order to test this hypothesis, culture conditions (i.e., temperature and food) were adjusted to induce active sexual reproduction of B. rotundiformis according to previous studies (Assavaaree et al, 2003;Hagiwara et al, , 1995Hirayama and Rumengan, 1993). In the presence of abundant and high quality food and an optimal temperature for rotifer population growth, the rotifers in the current study showed strong population growth compared to a natural population (<0.5 ind/mL, Snell et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…For organisms to survive and successfully colonize this area, they must possess certain physiological tolerances (Calder and Maÿal, 1997;Dumont, 1983;Nybakken, 2001;Saraswathy and Nair, 1974). The estuarine rotifer Brachionus rotundiformis Tshugunoff is capable of tolerating salinity variation like many other euryhaline zooplanktons (Assavaaree et al, 2003). We hypothesized that resting egg formation and hatching associated with seasonal changes of salinity could affect descendent sexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…However, a sudden drop in temperature from 23°C to 18°C resulted in high mortality of S‐type B. rotundiformis although they could withstand the sudden rise in temperature from 23°C to 28°C (Fielder, Purser & Battaglene ). While higher water temperatures of 30–35°C induced mixis in SS‐type B. rotundiformis , the rotifers exhibited higher growth rate and produced significantly more resting eggs at 25°C than at 30°C (Assavaaree, Hagiwara, Kogane & Arimoto ). In contrast, the larger L‐type rotifer, Brachionus plicatilis prefers cooler temperatures of 18–25°C (Hagiwara et al .…”
Section: Discussionmentioning
confidence: 99%
“…Assavaaree et al . () reported that B. rotundiformis fed with microalgae at 15 g L −1 salinity exhibited reduced growth rate and higher resting egg production when water temperature was brought down from 30 °C to 25 °C. Thus, a stable water temperature sustained in an indoor hatchery appears necessary to maintain a higher rotifer density.…”
Section: Discussionmentioning
confidence: 99%